What Behaviors “Strategic Teachers” Did for Pandemic-Era Modular Learning? An Exploratory Study with Basic Education Teachers in the Philippines - Española, Raymon P. (Journal of Community Development Research (Humanities and Social Sciences); Vol 16 No 2 (2023): April - June 2023DO - 10.14456/jcdr-hs.2023.12, 2023)
At the height of the pandemic, the Department of Education (DepEd) in the Philippines distributed self-learning modules to basic education students as part of its learning continuity program. This practice may have brought stress and challenges to many teachers, but this has also become a catalyst for creative problem-solving. This current study was designed to identify adaptive behaviors that were perceived to characterize “strategic teachers” in the midst of modular learning at the time of the pandemic. To address this objective, 120 statements were generated from narratives of four focus groups (N = 20 teachers). After content validation, 48 statements were retained and were administered to 429 basic education teachers (Mean age = 31.024; SD age = 7.466) through Google Forms. Exploratory factor analysis was done to analyze the data. Results revealed two subsets of teachers behaviors: 1) motivating students (“Establish good relationships with students by creating a non-threatening classroom environment”), and 2) using alternative delivery modalities (“Video-record lectures for students to watch”). These findings indicate that delivering student learning and managing academic motivation, related to key domains of the Philippine Professional Standards for Teachers (PPST), are necessary, hence shall serve as priorities for capacity building and enhancement training programs towards better basic education schools in the post-COVID world. Keywords: Teacher Behaviors, Basic Education, Exploratory Factor Analysis, Modular Learning, Post-COVID